The Leopard: from unpublished romance to bestseller - Zohreh Montaseri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Leopard is the only novel written by Giuseppe Tomasi di Lampedusa, born in Palermo in 1896. It was written between 1954 and 1957, but it has not been published immediately, because before Einaudi and then Mondadori refused to publish it. Only after the death of Tomasi, and thanks to Giorgio Bassani, in 1958 the publishing house Feltrinelli decided to publish the novel. A second edition, "in conformity with the manuscript of 1957", edited by Gioacchino Lanza, comes out in 1969. In 1959, the Leopard won the prize "Strega". Subsequently the novel becomes a bestseller and is translated into the whole world even in Persian. Despite the great passion for history and foreign novels, particularly French, Tomasi is dedicated to fiction only in the last years of his life.In this article, we will focus on the topics covered in the book and in particular the context in which the changes brought to Sicily are developed: expedition of the Thousand and the italy's unification.